1997
DOI: 10.1063/1.473357
|View full text |Cite
|
Sign up to set email alerts
|

The infrared spectrum of pyrazine in its metastable triplet state. A free-electron-laser study

Abstract: Vibrational transitions of pyrazine in the lowest triplet state have been observed as transient changes in the intensity of the phosphorescence induced by the free-electron laser FELIX. All seven fundamental infrared-active modes in the range of 250 to 1600 cm−1 have been detected and all vibrational frequencies are found to be considerably lower than the corresponding ones in the ground state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Tomer et al have tentatively assigned an observed line in the phosphorescence excitation spectrum observed at 800 cm -1 as the overtone band 11 1 0 16b 1 0 , suggesting 563 cm -1 for ν 11 . This frequency coincides with a very weak peak found by Kok et al at 565 cm -1 . Like ν 16b , ν 11 is of b 3u symmetry.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Tomer et al have tentatively assigned an observed line in the phosphorescence excitation spectrum observed at 800 cm -1 as the overtone band 11 1 0 16b 1 0 , suggesting 563 cm -1 for ν 11 . This frequency coincides with a very weak peak found by Kok et al at 565 cm -1 . Like ν 16b , ν 11 is of b 3u symmetry.…”
Section: Discussionsupporting
confidence: 91%
“…An asterisk indicates that the potential-energy surface is not a continuous function of that particular mode; i indicates an imaginary frequency, i.e., a transition state. b From Fischer, 17 except for those described in footnote c. c Our assignment of an observed 30 it a localized minimum-energy structure is found. The coordinate change was projected onto the CASSCF normal modes and found to be 2.2Q zpt , and this point is indicated in Figure 2.…”
Section: Singlet and Tripletmentioning
confidence: 91%
See 3 more Smart Citations